Calcineurin expression and localisation during porcine oocyte growth and meiotic maturation - Tůmová, Lenka; Petr, Jaroslav; Žalmanová, Tereza; Chmelíková, Eva; Kott, Tomáš; Tichovská, Hana; Kučerová-Chrpová, Veronika; Hošková, Kristýna; Jílek, František (Animal reproduction science, 2013)
The processes of oocyte growth, acquisition of meiotic competence and meiotic maturation are regulated by a large number of molecules. One of them could be calcineurin consisting of catalytic subunit A (Aα, Aβ, Aγ isoforms) and regulatory subunit B (B1, B2 isoforms). Calcineurin is involved in the meiotic maturation of oocytes in invertebrates or in lower vertebrates. In the mammalian oocytes, the possible role of calcineurin in the regulation of oocyte meiosis has not been clarified to date. In this study, to investigate the role of calcineurin during porcine oocyte growth, acquisition of meiotic competence and meiotic maturation, we analysed the expression and localisation of calcineurin subunits and the mRNA expression of calcineurin isoforms. Calcineurin was expressed in growing porcine oocytes, in fully grown oocytes and during their in vitro meiotic maturation. We found both subunits of calcineurin. Calcineurin A and calcineurin B were localised mainly in the cortex in all porcine oocytes. The changes in the intracellular localisation of separate calcineurin subunits during meiotic maturation were determined. We detected mRNA for calcineurin isoforms Aβ, Aγ, B2 in oocytes and mRNA for calcineurin isoforms Aβ, Aγ, B1, and B2 in cumular cells. To our knowledge, this is the first confirmation of calcineurin presence in porcine oocytes.
Keywords: messenger RNA; Meiotic competence; In Vitro Oocyte Maturation Techniques; transport proteinů; meióza; Oocyte; Gene Expression Regulation; Pig; Meiotic maturation; regulace genové exprese; Swine; Oocytes; ženské pohlaví; RNA, Messenger; zvířata; oocyty; IVM techniky; Meiosis; kalcineurin; Protein Transport; prasata; Growth period; Female; Calcineurin; Animals